Multidisciplinary approach to pest management and the African farmer - Okigbo, B. (1974)
Ecological consideration indicate that traditional agroecosystems involving mixed cropping and genetic diversity among crop species are relatively more stable than modern agroecosystems. Modern food production technologies involving more uniform crops over wide areas, use of more costly inputs and associated pest problems are ecologically less stable. With population pressure, greater pressures on the land and shortening of periods of natural recycling of nutrients reduced yields and loss of soil fertility occur. This calls for introduction of modern, farming techniques of the 'green revolution' type. Yet the experience of developed countries in about three decades of over-reliance on chemical pesticides, the development of resistance in target species, and environmental hazard of pesticides require caution in development of pest management control programs. What is needed is a program of integrated control or effective pest management as part of an overall natural resource management. This necessitates greater cooperation and interaction among scientists in various disciplines in the study of the environment, tropical a9roeGosystems, and development of a range of compatible pest control methods within the means of the farmer, economically and technologically acceptable, and adapted to various agro-ecosystems. All these require (i) changes in biological education and training, (ii) better communication among scientists and the public, and (iii) provision of better advisory services to government policy am regulatory agencies.